Shared Visions: Evaluating Potential in Unsettled Fields - Olofsson, Tobias ; 0000-0002-0289-1826; Gerber, Alison ; 0000-0002-1357-3516 (Minerva, 2025)
Issues of quality, value, and merit are perpetually lively and contentious in scientific and academic work, and research on evaluation panels have shown that organizational constraints and the methods of evaluation used, whether well-motivated or adopted ad hoc, have enormous influence on outcomes. But while previous studies have highlighted the influence exerted by particular methods of evaluation or by social psychological factors, this study shows how in conditions of high uncertainty assessors’ speculative work allows them to project and establish consensus on indicators of quality. Drawing on ethnographic fieldwork with a national science council, we focus especially on the challenges of evaluating speculative genres of academic writing. We look to evaluations of research proposals in the field of artistic research in order to highlight the ways that evaluators project and establish consensus on indicators of quality in relation to the uncertainties inherent in speculative scientific writing. We show how successful applications outline particular visions of the future, visions that can be accommodated within evaluators’ understanding of the discipline itself well enough that evaluators can suspend disbelief regarding the future outcomes of the proposed research. In doing so, we exploit the emergent and unsettled nature of artistic research as a discipline to highlight the impact of the future in evaluation processes: the function of panelists’ visions of their discipline at its best in the present, and their imaginaries of the discipline of the future.